AIR VELOCITY AND PRESSURE MEASUREMENTS OF PORTABLE AIR PURIFIERS USING NUMERICAL SIMULATIONS BASED ON PRODUCT COMPONENT DESIGN VARIATION - Iskandriawan, Bambang; Safaat, Ahmat; Tristiyono, Bambang (Journal of Applied Engineering Science, 2025)
It is of great importance to ascertain the airflow pattern around a device that functions by blowing out air, as the resulting airflow pattern will ultimately determine the device's performance. The airflow pattern surrounding an air purifier is greatly influenced by the product design of its constituent components, especially the blow air diffuser and the return air components. Given the growing and, to some extent, compulsory usage of portable air purifiers among the general public, especially among those concerned with maintaining good indoor air quality, this study aimed to identify the optimal product component design for portable air purifiers. This was achieved by considering the effects of air velocity and pressure on the performance of the air purifiers. In this study, a numerical simulation application was employed to obtain data on air velocity ​​and pressure for each product component design variation. The objective was to generate a report on air velocity and pressure for various component design variations of high-efficiency particulate air (HEPA) filters, including variations in height and diameter, rotor blade tilt angle and width, and inlet hole casing design pattern.
Keywords: air velocity and pressure measurements, portable air purifier, numerical simulations, product component design variations, airflow pattern